Acceptability of ecological momentary assessment among young men who have sex with men - Duncan, Dustin T.; Kapadia, Farzana; Kirchner, Thomas R.; Goedel, William C.; Brady, William J.; Halkitis, Perry N. (Journal of LGBT youth, 2017)
The study evaluated the acceptability of text message- and voice-based ecological momentary assessment (EMA) methods among a sample (N = 74) of young men who have sex with men (MSM). We assessed the acceptability of text message- and voice-based EMA methods. Almost all participants (96%) reported that they would be willing to accept texts on their smartphone to answer questions about their current mood, surroundings, or feelings. A large majority (89%) also reported being willing to accept phone calls to answer these questions. This work suggests that different EMA methods are acceptable for use among young MSM.